Grafting of manganese phthalocyanine on nanocrystalline diamond films. Issue 10 (17th September 2013) - Petkov, Christo; Glebe, Ulrich; Petkov, Emil; Pasquarelli, Alberto; Pietzka, Carsten; Veres, Miklos; Himics, Laszlo; Merz, Rolf; Kulisch, Wilhelm; Siemeling, Ulrich; Reithmaier, Johann Peter; Popov, Cyril
<x xml:space="preserve">Abstract</x> Thin boron‐doped nanocrystalline diamond (NCD) films have been prepared by microwave plasma enhanced chemical vapour deposition (MPCVD) and used as platforms for grafting of photosensitizer (manganese phthalocyanine, Mn‐Pc). The surface of the as‐grown films is H‐terminated; in order to modify it and study the influence of the termination on the attachment of Mn‐Pc the NCD films were subjected to O2 plasma or NH3/N2 plasma treatments. Contact angle measurements and XPS results showed a successful exchange of the surface termination with OH‐ or NH2‐groups. Manganese phthalocyanine molecules were grafted on the NCD surfaces with different terminations, after which each sample was subsequently characterized by XPS and Raman spectroscopy. Finally, the NCD/Mn‐Pc samples were used for the preparation of electrodes which were tested in an electrochemical cell with a Pt counter electrode and an Ag/AgCl reference electrode; phosphate buffered saline was used as electrolyte. The characteristics of the electrodes were measured by cyclic voltammetry (CV) and open circuit potential (OCP) in dark and under illumination with a light‐emitting diode (LED) operating at 770 nm (a wavelength close to the absorption maximum of Mn‐Pc). The first results indicated that after plasma modifications NCD surfaces are suited for Mn‐Pc grafting.